2022
DOI: 10.1093/jjco/hyac086
|View full text |Cite
|
Sign up to set email alerts
|

Oral histone deacetylase inhibitor HBI-8000 (tucidinostat) in Japanese patients with relapsed or refractory non-Hodgkin’s lymphoma: phase I safety and efficacy

Abstract: Objective HBI-8000 (tucidinostat) is a novel, oral histone deacetylase inhibitor that selectivity inhibits Class I (histone deacetylase 1, 2, 3) and Class II (histone deacetylase 10) with direct anti-tumor activity through various mechanisms of action, including epigenetic reprogramming and immunomodulation. It has been approved in China for the treatment of relapsed or refractory peripheral T-cell lymphoma. Methods This mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…In the present study, the dose of 40 mg BIW was determined based on the results from the phase I study of Japanese patients with non-Hodgkin lymphoma, in which 40 mg BIW was tolerable and the ORR for the 40 mg cohort was higher than that for the 30 mg cohort. 31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the dose of 40 mg BIW was determined based on the results from the phase I study of Japanese patients with non-Hodgkin lymphoma, in which 40 mg BIW was tolerable and the ORR for the 40 mg cohort was higher than that for the 30 mg cohort. 31 …”
Section: Discussionmentioning
confidence: 99%
“…Identifier: NCT02953652 ). The dose, 40 mg twice per week (BIW), was determined based on the result from the preceding phase I study for Japanese patients with non-Hodgkin lymphoma, 31 which was higher than that approved for patients with PTCL in China (30 mg BIW). The data described herein led to the approval of tucidinostat for R/R PTCL by the Japanese Ministry of Health, Labour and Welfare in 2021.…”
Section: Introductionmentioning
confidence: 99%
“…For example, functional dysregulation of histone acetyltransferases has been associated with cancer development, including B-cell [45,46] and T-cell lymphomas [47,48]. In humans, histone modifier gene mutations have been associated with inferior progression-free survival time in patients with T-cell lymphomas [48], and it has been demonstrated that HDAC regulates the expression of BCL6, involved in cell survival and/or differentiation in B-cell lymphoma [49], and HDAC inhibitors have been tried as therapy in humans [50][51][52]. In CML, repression of p16 tumour suppressor gene is regulated by histone H3 acetylation in vitro [53].…”
Section: Histone Modificationsmentioning
confidence: 99%
“…Tucidinostat (chidamide), as a Class I HDAC inhibitor, has been shown to inhibit a variety of cancer growth [ 41 , 42 , 43 , 44 , 45 , 46 ]. Therefore, we selected Tucidinostat in our in vitro cell model to assess its effect on uLMS cell growth.…”
Section: Resultsmentioning
confidence: 99%